THE ROLE OF FORUM ON CHINA-AFRICA COOPERATION (FOCAC) IN INCREASING SOUTH AFRICA'S FOREIGN DIRECT INVESTMENT (FDI) IN 2018-2021 - Bela Sofia (Mediasi: Journal of International Relations, 2022)
This study examines the role of the Forum on China-Africa Cooperation(FOCAC) in increasing Foreign Direct Investment (FDI). FOCAC was formed aninstrument for China in encouraging its country's economic growth, throughcooperation with South Africa where the country is classified as developingcountry and has abundant Natural Resources (HR). This study purpose tounderstand how big the role of the FOCAC organization in increasing FDI inSouth African countries, through the framework of International Cooperation,especially Multilateral Cooperation between China and South Africa. This studyuses qualitative approach applying by descriptive analysis that takes fromsecondary data sources. The results showed that the role of FOCAC was able toprove that South Africa's investment surplus increased, especially from 2018 to2021. Foreign Direct Investment is support for South Africa to rebuild itscountry's economy, while FOCAC a vessel for China. -Africa in carrying outcooperation that applies the law and mutual respect between the two, this is in linewith the concept of Islamic economic growth which emphasizes the commongood in achieving mutual benefits. Meanwhile, in international relations, foreignpolicy plays role in building investment and the Gross Development Product(GDP) which purpose to prosper the people.